Glycerine degradation by submerged plasma. (29th August 2019) - Essiptchouk, A; Petraconi, G; Miranda, F; Saraiva, A C V; Charakhovski, L
Abstract: Organic contaminants (for example in wastewater effluents) cause serious health and environmental problems due to their high chemical oxygen demand (COD), low biodegradability, and toxicity. Non-equilibrium and thermal plasmas were actively studied and numerous reactor geometries were developed to induce chemical reactions in treated liquids. Thermal plasma, because of its elevated temperatures and presence of highly active radicals, accelerates kinetics of chemical reactions and achieve high destruction efficiencies in processing of gaseous, liquids and solid materials. In this work, a plasma-chemical reactor, with submerged plasma jet for treatment of liquid residues, is presented and applied for treatment of water contaminated with glycerine. A distinctive feature of submerged plasma treatment is the high local plasma temperature and low treated liquid temperature, which promotes high quenching rate that preserves radical concentration and promotes advanced oxidation of aqueous effluents in highly turbulence flow. This work presents the main functioning characteristics of the reactor and the effect of specific energy input on glycerine degradation by thermal plasma.